Biomarkers of sleep disturbance in adults with chronic illness: A scoping review. (March 2023) - Winders, Samantha; Lyon, Debra E.; Stechmiller, Joyce K.; Kelly, Debra Lynch
Objectives: The purpose of this scoping review was to identify which biomarkers for sleep disturbance were the most prevalent and significant in the literature across chronic illnesses. Methods: A scoping review was conducted, following Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) guidelines, to provide a map of the existing literature on the biomarkers of sleep disturbance in adults with chronic illness. Peer-reviewed articles published between 2010–2020 were included if they measured a biomarker and discussed sleep deprivation, disturbance, or dysfunction secondary to a chronic illness. Results: A total of 21 articles were included and synthesized using data charting. There were 24 different biomarkers identified, most commonly collected through serum. Biomarkers were grouped, then biomarkers and correlations with sleep were identified and mapped. Discussion: Overall, the most common biomarkers studied were interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), c-reactive protein (CRP), and interleukin-1 beta (IL-1β). Cytokines were the most commonly studied biomarkers, with a majority of studies focusing on pro-inflammatory cytokines. Based on the results of this review, CRP, IL-6, TNF-α, and erythrocyte sedimentation rate (ESR) showed themost significant correlations with sleep across all chronic illnesses. Future research is still needed to identify an ideal biomarker for sleep disturbance that can be used across chronic illnesses.